Creativity in Innovative Teaching, the Role of Teachers in Integrating Creativity and Critical Thinking Through Technology - Albana Tahiri (Journal of Pedagogical and Teacher Professional Development, 2025)
Innovative teaching and creativity play a fundamental role in fostering critical thinking and creative skills among students. In alignment with the Sustainable Development Goals, education must implement strategies that encourage exploration, collaboration, and active student engagement. The integration of technology in the teaching process presents a valuable opportunity to enhance instructional effectiveness; however, a significant challenge remains the lack of technological competencies among teachers, particularly in rural areas. This study is grounded in constructivist theory and employs a mixed-methods approach, combining qualitative and quantitative research. To collect relevant data, interviews and focus groups were conducted with teachers and students, while surveys were administered to 784 students and 70 teachers from urban and rural schools in Tirana. To ensure the reliability and validity of the research instruments, the questionnaires were piloted with 50 pre-service teaching students. The results indicate that creative teaching methods and technology integration positively impact student engagement and the development of critical thinking skills. However, a considerable number of teachers face challenges in incorporating technology into their teaching practices. Therefore, it is recommended that continuous professional development programs be implemented for teachers and that digital platforms be effectively integrated into the education system to enhance teaching and learning quality.